Semantic relation of medieval Turkic written monuments and modern Kazakh languages proverbs - Amantay Zh. SharipZhanna Аlashbayeva,Мagripa K. YESKEYEVA, Bauyrzhan Zh. Omarov,; Otelbay, Gulbaira T. (Opción, 2020)
The study aims to investigate medieval Turkic’s semantic relation written monuments and modern Kazakh language proverbs. The theoretical and methodological basis of the research is the works of Turkic-linguists, written in the language of medieval monuments. As a result, the Turkish language has been brought until this century without prejudice, preserved as a treasure and the credit has to be gone to Kazakh. In conclusion, because of some historical events in the fate of the nation, ethnonyms specific to a particular nation was imposed and preserved in the memory of the people.